Proposal of a Business Process Architecture (BPA) development method for supporting the transition of manufacturing companies into Product-Service System (PSS) providers - Pieroni, Marina de Pádua (2017)
In order to stay competitive and to create value to their clients, manufacturing companies are engaging in a process called servitization, which consists in transforming their existing physical product offerings into integrated bundles of products and services, called Product-Service Systems (PSS). Servitization compels manufacturing companies to change their business models. One of the main challenges of servitization is to redesign the business processes dimension of their business model in order to operate middle of life (MOL) and end of life (EOL) phases of PSS. Despite the existence of decades-long successful PSS cases, operational difficulties are still reported. This is associated to gaps in existing PSS business model design methodologies, which are focused on the development of new PSS and lack the required level of details for servitization. The goal of this study is to propose a method to support manufacturing companies during the servitization process in developing a PSS Business Process Architecture (PSS BPA), which is the basis for redesigning their business processes. The method was developed with the support of the Design Research Methodology (DRM), which comprises four research stages. In the first and second stages, a literature review was conducted to generate theoretical requirements for guiding the proposition of the PSS BPA Development Method. Action research approach was applied in the third stage to propose the PSS BPA Development Method empirically. Action research was carried in a large multinational manufacturing company from the healthcare sector, which intended to transform a diagnostic imaging product into a use-oriented PSS. In the last stage, the method received a preliminary assessment with the intent of being prepared for further applications in case studies. The results indicate that the PSS BPA Development Method has a potential for supporting companies in defining their PSS BPA. Other key contributions of the research were the proposition of a business process reference model for PSS based on the Process Classification Framework (PCF), and insights and findings obtained with the real case of servitization.